Postictal serotonin levels are associated with peri-ictal apnea. (8th October 2019) - Murugesan, Arun; Rani, M.R. Sandhya; Vilella, Laura; Lacuey, Nuria; Hampson, Johnson P.; Faingold, Carl L.; Friedman, Daniel; Devinsky, Orrin; Sainju, Rup K.; Schuele, Stephan; Diehl, Beate; Nei, Maromi; et al.
Abstract : Objective: To determine the relationship between serum serotonin (5-HT) levels, ictal central apnea (ICA), and postconvulsive central apnea (PCCA) in epileptic seizures. Methods: We prospectively evaluated video EEG, plethysmography, capillary oxygen saturation (SpO2 ), and ECG for 49 patients (49 seizures) enrolled in a multicenter study of sudden unexpected death in epilepsy (SUDEP). Postictal and interictal venous blood samples were collected after a clinical seizure for measurement of serum 5-HT levels. Seizures were classified according to the International League Against Epilepsy 2017 seizure classification. We analyzed seizures with and without ICA (n = 49) and generalized convulsive seizures (GCS) with and without PCCA (n = 27). Results: Postictal serum 5-HT levels were increased over interictal levels for seizures without ICA ( p = 0.01), compared to seizures with ICA ( p = 0.21). In patients with GCS without PCCA, serum 5-HT levels were increased postictally compared to interictal levels ( p < 0.001), but not in patients with seizures with PCCA ( p = 0.22). Postictal minus interictal 5-HT levels also differed between the 2 groups with and without PCCA ( p = 0.03). Increased heart rate was accompanied by increased serum 5-HT levels (postictal minus interictal) after seizures without PCCA ( p = 0.03) compared to those with PCCA ( p = 0.42). Conclusions: The data suggest that significant seizure-related increases in serum 5-HT levels are associated with a lower incidence of seizure-related breathing dysfunction, and may reflect physiologic changes that confer a protective effect against deleterious phenomena leading to SUDEP. These results need to be confirmed with a larger sample size study.